Online Slot Games Addiction Phenomenon Case Study of Cultural Anthropology Students Batch 2020 Isi Padangpanjang - Natasha Meiliza; Mutia Kahanna; Septriani (Kirana Publisher (KNPub), 2024)
This research discusses the phenomenon of game online slot addiction, a case study of Cultural Anthropology students class of 2020 at ISI Padangpanjang. The aim of this research is to describe the factors behind and the consequences of the online slot game addiction phenomenon in Cultural Anthropology students class of 2020 at ISI Padangpanjang. The theories used are Alfred Schutz's Phenomenology theory and Dominic Strinanti's Popular Culture theory. The research method used is qualitative research. Data collection techniques are field observations, interviews and documentation. The findings from this research are that there are several factors that make Cultural Anthropology students class of 2020 addicted to playing online game slot online, such as: high curiosity, trying out luck, filling in gaps, and a friendly environment. Then the consequences caused by gameslotonline addiction include dependency, lack of sleep and disturbed activities, not focusing on studying and talking dirty and rude.